Attributes of female tennis champions and challenges faced by aspirants - Young, J. A.; Pearce, A. J. (Medicine and Science in Tennis, 2009)
As part of a larger study on talent development in tennis, 10 Australian top ranked Australian female professional tennis players responded to a questionnaire about the attributes of a champion recalling the major challenges faced in pursuing a tennis career and strategies adopted to address these challenges. To analyse the data, a series of three inductive content analyses were conducted. The results highlighted the importance of psychological attributes and skills in a player`s journey to become a champion. The study`s implications for coaches and sport psychologists are also highlighted.